Psychosocial Problems among Nurses in Patient’s Care of COVID-19: A Literature Review - Nurfika Asmaningrum; Atifah Adha Manurung; Dicky Endrian Kurniawan (Nursing and Health Sciences Journal (NHSJ), 2021)
Coronavirus Disease 2019 (COVID-19) had an impact on a health crisis, thus posing a major threat to the health of nurses. Nurses was at risk for psychosocial problems while caring for COVID-19 patients. The aims of this study was to analyzed the psychosocial aspects that occured to nurses when caring for COVID-19 patients during the pandemic. Searching articles used five databases such as Google Scholar, Proquest, ScienceDirect, PubMed, and Taylor & Francis Online. Research designs used cross-sectional and qualitative. The findings in this study were divided into two themes, namely the form of nurses psychosocial responses when caring for COVID-19 patients such as viral contamination, abnormal separation, decreased immunity, social pressure, and uncertainty and strategies for nurses' psychosocial handling efforts when caring for patients COVID-19 such as social support, participation in training, support groups, calming activities, and improving the quality ofresources. The condition of psychosocial problems experienced by nurses when caring for COVID19 patients will be expected to be able to carry out effective coping strategies such as promotive, preventive, curative, and rehabilitative so that nurses are able to adapt during pandemic to improve the quality of effective services.